Analisis Semiotika Dalam Iklan Rokok “Wismilak Diplomat - Switch To Success, Arti Sebuah Kesuksesan”: Kajian Semiotika Roland Barthes - Fery Mursyidan Baldan; Rizki Endi Septiyani (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
The modern era makes the line aspect must undergo a change and adjustment based on the times, including in terms of commercial advertising of a product. This study aims to find out the markers and markers in the Wismilak Diplomat - Switch to Success advertising video and to find out the myths that you want to build in the Wismilak Diplomat - Switch to Success cigarette ad video insert based on Roland Barthes' semiotic analysis. The method used in this study is a qualitative descriptive method with data collection techniques through documentation, video analysis, and reading related sources related to research by examining the meaning of denotation, connotation, and myths from related data sources. The results of this study are the exposure of semiotic analysis in the form of denotation, connotation, and myths contained in the Wismilak Diplomat cigarette advertisement video - Switch to Success.